GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP INFORM CONSENT TINDAKAN SEKSIO SESAREA DI RUMAH SAKIT JEJARING FK UMSU - MUHAMMAD HAFZUL FAUZY; RAHMANITA SINAGA (LP2MTBM MAKARIOZ, 2021)
Inform consent is the provision of information, treatment plan recommendations, patient understanding, voluntary decisionmaking, and authorization to proceed with the treatment plan. Patient informed consent is a prerequisite for all surgicalprocedures. Any medical action carried out without informed consent is a violation of the law and the doctor himself can beprosecuted criminal or civil suit. To find out the description of the level of patient satisfaction with informed consent forcesarean section. FK UMSU network hospital. The design used in this study is cross sectional, using validatedquestionnaires towards 60 respondents. The overall level of patient satisfaction with the informed consent of cesareansection in the FK UMSU network hospital is satisfied with an average of 96.7%.